2006
DOI: 10.1007/s11434-006-2175-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical mechanism responsible for the stay-green phenotype in common wheat

Abstract: In order to increase the supply of assimilated carbon to grain, a new stay-green wheat cultivar, Chuannong17 (CN17), with delayed leaf senescence, carrying wheat-rye 1RS.1BL translocated chromosome was developed. CN17 exhibited distinct differences in net photosynthetic rate (P n ), chlorophyll (Chl) content, malondialdehyde (MDA) content, activity of both superoxide dismutase (SOD) and catalase (CAT) during the grain filling stage, and flag leaf senescence compared with the control. The new cultivar maintaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…Delayed leaf senescence can prolong the supply of assimilated carbon to grains during the grainfilling period, thereby ensuring maximum mass per grain. For instance, CN17 is another stay-green wheat mutant reported (Luo et al 2006). MY11 was the most important agronomical parent in the pedigree of CN17.…”
Section: Tasg1 Is a Functional Stay-green Mutant With The Characterismentioning
confidence: 99%
“…Delayed leaf senescence can prolong the supply of assimilated carbon to grains during the grainfilling period, thereby ensuring maximum mass per grain. For instance, CN17 is another stay-green wheat mutant reported (Luo et al 2006). MY11 was the most important agronomical parent in the pedigree of CN17.…”
Section: Tasg1 Is a Functional Stay-green Mutant With The Characterismentioning
confidence: 99%
“…Spano et al (2003) reported that functional stay-green mutants of durum wheat maintained longer photosynthetic activity, had higher seed weights, and yielded more grain than the parental genotype. Luo (2006) also reported a new stay-green wheat cultivar "CN17" with delayed leaf senescence maintained longer and higher photosynthetic competence compared with the control cultivar and this aspect was correlated with the difference in chloroplast development.…”
mentioning
confidence: 86%
“…These translocations had been previously characterized using various cellular and molecular analyses (Luo et al 2006(Luo et al , 2013Zhang et al 2008). However, more studies are needed to better understand the mechanism underlying the origin of these novel traits and to obtain information about the involvement of 1BL/1RS translocation in the adaptation of plants to stress conditions.…”
Section: Introductionmentioning
confidence: 99%